Synthesis of Non‐precious N‐doped Mesoporous Fe3O4/CoO@NC Materials towards Efficient Oxygen Reduction Reaction for Microbial Fuel Cells. Issue 8 (9th February 2022) - Jiang, Bolong; Lu, Decheng; Jiang, Nan; Jiang, Hailin; Qi, Lihua; Shi, Shunjie; Cui, Yanyan; Tan, Weiqiang
Abstract: N‐doped transition metal oxides are strategic materials towards the efficient oxygen reduction reaction (ORR) of microbial fuel cells (MFCs). Non‐precious N‐doped Fe3 O4 /CoO@NC−T (T represents carbonization temperature) catalysts are prepared by an efficient two‐step strategy for ORR. Fe3 O4 /CoO@NC‐750 exhibits the best performance with an efficient four‐electron transfer pathway. The optimal power density of MFCs by using Fe3 O4 /CoO@NC‐750 as the cathode catalyst (1243.4 mW ⋅ m −2 ) is superior to that of the MFCs with commercial Pt/C catalyst (1080 mW ⋅ m −2 ), which shows an outstanding activity towards ORR. No significant decrease in output voltage results over 70 days, which shows an excellent electrochemical stability. Abstract :